Physical properties, characterization and interaction mechanism study between barium sulphate and diethylenetriaminepentaacetic acid pentapotassium salt - Sapiyah , Mohd Sukri (2015)
The scale formation of inner pipe was a common problem in oil and gas production industries. This problem resulted in decreasing in the amount of oil and gas produced and production efficiency, formation damage, emergency shutdown, equipment failure and increase the maintenance cost. The deposition of scale often resulted from the incompatibility between injected saline water and reservoir water. The common scales formed in the oil field are CaCO3, CaSO4 (anhydrite, gypsum), BaSO4 (barite), SrSO4 (celestite) and ferrous scale. Among the scales, BaSO4 was the hardest scale and difficult to remove chemically or mechanically. Thus, a suitable chelating agent needs to be identified in order to overcome this problem. In this present study, the physical properties, characterization and interaction mechanism between BaSO4 and Diethylenetriaminepentaacetic acid pentapotasium salt (DTPA) used as solvent were investigated. Based on the findings, the pH value of pure DTPA and DTPA-BaSO4 mixture were same which were 14.00. On the other hand, the pure DTPA viscosity was 7.28 mPa.s and based on the observation, the DTPA-BaSO4 mixture was identified less viscous than the pure DTPA. The density for pure DTPA was 1.787 g/ml and the mixture of DTPA and BaSO4 were expected to increase as the mass of solute increase. The amount of water content for both samples did not change which was 54.10 %. Besides that, the CHNS and ICP-MS results represented the structure of DTPA. In addition, the interaction mechanism study based on the FTIR and NMR analysis showed that DTPA and BaSO4 having hydrogen bonding interaction at CH2 functional group.